2005
DOI: 10.1111/j.1439-0531.2005.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Oestrogen Receptors α and β and of Aromatase in the Testis of Immature and Mature Boars

Abstract: The boar testis secretes high amounts of oestrogens. In order to test for a likely local significance, we investigated the expression of oestrogen receptors (ER) in immature and mature boar testes using immunohistochemistry (IHC), in vitro and in situ reverse transcription-polymerase chain reaction (RT-PCR). Samples were from 25 boars castrated at ages of 50, 100, 150, 200 and 250 days. Mouse monoclonal primary antibodies against porcine ERalpha (clone HT227), human ERbeta1 (clone PPG5/10) and human P450 aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 59 publications
(65 reference statements)
6
59
0
Order By: Relevance
“…A change of aromatase expression was demonstrated in early postnatal rats, where aromatase is expressed in Sertoli cells but its expression shifts to Leydig cells in mature rats (Tsai-Morris et al 1985). The pig is unique due to its high amounts of estrogens (Claus et al 1985), which are exclusively synthesized in Leydig cells of mature boars (Mutembei et al 2005). The present study presents first data on aromatase localization by immunocytochemistry in fetal pigs.…”
Section: Discussionmentioning
confidence: 85%
“…A change of aromatase expression was demonstrated in early postnatal rats, where aromatase is expressed in Sertoli cells but its expression shifts to Leydig cells in mature rats (Tsai-Morris et al 1985). The pig is unique due to its high amounts of estrogens (Claus et al 1985), which are exclusively synthesized in Leydig cells of mature boars (Mutembei et al 2005). The present study presents first data on aromatase localization by immunocytochemistry in fetal pigs.…”
Section: Discussionmentioning
confidence: 85%
“…ERs play an important role in activating signaling pathways leading to sperm capacitation, essential for further successful fertilization. ERs have been detected in the sperm of many species, for example, human (Aquila et al 2004, Solakidi et al 2005, boar (Mutembei et al 2005), rooster (Kwon et al 1995), rat (Pellettier et al 2000), but failed to be detected so far in mouse spermatozoa. In this study, the 64 kDa protein corresponding to ERB was detected to be present in sperm from cauda epididymis using immunoprotein detection.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of multiple regression relations showed that the levels of testicular hormones testosterone, estrone sulphate and free estrone in combination with testes and bulbo-urethral gland sizes were the best predictors of skatole in fat (Zamaratskaia et al, 2005d). The boar is known for its high amounts of estrogens (Claus and Hoffmann, 1980), which are produced in testicular Leydig cells (Raeside and Renaud, 1983;Mutembei et al, 2005) and are positively correlated to skatole levels Zamaratskaia et al, 2005c).…”
Section: Androstenone Skatole and Hormonal Status Of Animalsmentioning
confidence: 99%